Classroom walkthrough observations in a state university: On grounded theory - Annalene Grace Edu Co; Roselle Matammu Soriano (International Journal of Evaluation and Research in Education (IJERE), 2022)
The primary goal of this classroom walkthrough observation study was to come up with a theoretical framework that improves the instruction process in a public university in Region 02, Philippines. Walkthroughs in classrooms are done quickly and unexpectedly, usually by school administrators in the facility. In addition to deans and program chairpersons, nine educational leaders (deans and program co-chairs) and 37 faculty members took part in the study by the chain or snowball sampling. A core category (phenomena) was formed, conceptual tags were assigned, and a theoretical model that describes the causal elements influencing the phenomenon was developed through extensive discussions. Strategies that arise as a result of the occurrence, processes affected by context, processes that are influenced by intervening conditions, and implications of the system when employed. A detailed description of the many categories and subcategories are given, and participants' statements in support of the theory.